Low-Dose Gemcitabine Treatment Enhances Immunogenicity and Natural Killer Cell-Driven Tumor Immunity in Lung Cancer - Zhang, Xin; Wang, Dong; Li, Zhidong; Jiao, Defeng; Jin, Linlin; Cong, Jingjing; Zheng, Xiaohu; Xu, Lijun (Frontiers in Immunology, 2020)
Gemcitabine has been used as first-line chemotherapy against lung cancer, but many patients experience cancer recurrence. Activation of anti-tumor immunity in vivo has become an important way to prevent recurrence. Anti-tumor immune responses are often dependent upon the immunogenicity of tumors. In our study, we observed that low-dose gemcitabine treatment enhanced the immunogenicity of lung cancer by increasing the exposure of calreticulin, high mobility group box 1, and upregulating expression of NKG2D ligands. Further studies demonstrated that low-dose gemcitabine treatment increased interferon-γ expression and NK-cell activation in mice. Low-dose gemcitabine treatment was sufficient for inhibiting tumor growth with few side effects in vivo. These data suggest that low-dose gemcitabine-induced immunochemotherapy activated antitumor immunity in immunocompetent patients.